Bidri Art And the Harmony of Cultures: An Indo-Islamic Synthesis - Anitha Patil T.H., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Bidri Art, though of Persian origin, is a unique Indo-Islamic synthesis and purely an Indian innovation, flourishing under the Bahamani and Baridi dynasties, particularly in Bidar. Its history traces back to the 15th century when Sultan Allauddin-II patronized Bidri workers from Bijapur, including the first Indian artisan, Shivanna. The art form, named 'Bidriware' by the Sultan, involves casting an alloy (primarily zinc and copper) followed by intricate silver and gold inlay work. The specialized blackening process, utilizing a mixture of local fort clay, is distinctive. Bidriware represents a harmonious blend of Hindu and Muslim craftsmanship, with artisans contributing diverse motifs—from Hindu figures to Persian flowers and geometric patterns. Though once widespread, the craft is now facing extinction and requires urgent support.
Keywords: Bidri Art; Indo-Islamic; Bidar; Inlay; Shivanna